PEMBELAJARAN FUN SCIENCE EXPERIMENT DALAM PENGEMBANGAN KREATIVITAS ANAK USIA DINI DI TK PERTIWI BOJONGSARI KECAMATAN KEMBARAN KABUPATEN BANYUMAS - Susi Susanti; Wahyu Purwasih (STPI Bina Insan Mulia Yogyakarta, 2023)
Learning by implementing fun experiments, need motivation from teachers and parents. The development of children's creativity through experiments requires adequate and supportive facilities and infrastructure. The purpose of this study was to find out the fun science experiment learning that was applied by teachers in developing early childhood creativity. This study used a field research method that is descriptive qualitative in nature. The location studied was Pertiwi Bojongsari Kindergarten, Kembaran District, Banyumas Regency. The research subjects included teachers in group B2, children in group B2, and parents in group B2. The results of research on Fun Science Experiment Learning in the Development of Early Childhood Creativity at Pertiwi Kindergarten Bojongsari, Kembaran District, Banyumas Regency, namely: 1) Learning by applying sinking and floating experiments, color sand experiments, rainbow tissue experiments, color milk or milk experiments rainbows, and experiments with wind-powered cars have a positive impact on the development of children's creativity. Attitudes and creative ideas of children emerge with the application of experiments. 2) Supporting and inhibiting factors come from within the child and from outside such as physical and psychological conditions, facilities and infrastructure, as well as the role of teachers and parents in learning fun science experiments that are applied by teachers in developing early childhood creativity.